Brucellosis outbreak in a remote village in northwestern Tajikistan in 2023: a matched case-control study - Qurbonov, Emomali; Silemonshoeva, Jamila; Horth, Roberta; Tilloeva, Zulfiya; Yusufi, Salomudin; Nabirova, Dilyara (Frontiers in Epidemiology, 2024)
Background: A sharp increase in reported brucellosis incidence was observed in northwestern Tajikistan (from 1.0/100,000 people in January-May 2022 to 32.7/100,000 in January-May 2023).Most (82%) cases were from the same remote mountainous village (population=10,712). The aim of this study was to identify risk factors for brucellosis infection and mitigate disease risk.Methods: Using a case-control design, we conducted face-to-face interviews and collected blood samples during May-June 2023. Fifty-seven cases and 114 controls were recruited. Cases were the first person in a household diagnosed with brucellosis during February-June 2023 with positive serum agglutination test and antibody titers ≥1/160 from blood samples. Two controls were selected for each case (neighbors from different households matched by age and sex).Controls testing positive were excluded and replaced. We conducted conditional multivariable logistic regression to calculate adjusted odds ratio (AOR) and 95% confidence intervals (CI).Results: Among the 87 brucellosis patients reported, 57 (66%) agreed to participate and didn't have secondary cases in the household. Of the 57 cases, 68% were 15-44 years old, and 44% were male. Cases peaked in May 2023. Common symptoms were joint pain (95%), fever (84%), weakness (72%), and night sweats (65%). Of selected controls, 13% tested positive and were excluded. All cases and 94% of controls owned livestock (mostly cattle, sheep, or goats); no animals had not been vaccinated in the past 5 years. Brucellosis was associated with consumption of both homemade kaymak (clotted cream) and home-raised meat compared with neither (AOR: 59 [95%CI: 4.3-798], p<0.01), home-raised meat but not kaymak compared with neither (AOR: 54 [4.0-731], p<0.01), and involvement in animal slaughter compared with no involvement (AOR: 36 [2.8-461], p<0.01).Contact with unvaccinated livestock or consumption of their products was a key contributor to this outbreak in a remote village of Tajikistan. With 13% of controls testing positive, true incidence was likely greater than reported. Following our investigation, a brucellosis awareness education campaign and animal vaccination campaigns were carried out in the region and only one case was reported in September 2023.